A student satisfaction framework for evaluating quality and priority service in management of open and distance education in Indonesia / Rini Dwiyani Hadiwidjaja ... [et al.] - Hadiwidjaja, Rini Dwiyani; Suroso, Arif Imam; Siregar, Hermanto; Sailah, Illah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
Service quality plays an important role in customer perception as it contains information about satisfaction. With the Covid-19 epidemic, satisfaction has become relevant for students participating in Open and Distance Education (ODE) practice. This study aimed to evaluate the quality and the priority service in the management of ODE during normal and pandemic period in Indonesia. 719 students and experts from Universitas Terbuka (UT) were surveyed as part of the qualitative and quantitative methodology. Service Quality was measured by five dimensions and student satisfaction. The Gap Analysis and Importance-Performance Analysis Matrix were employed in this study. The findings showed that the performance of UT services needs to be improved. The normal and pandemic periods did not differ in any significant manner. The IPA matrix showed the priority service improvement in the management of changes made is to focus on the capability of the lecturer. During the pandemic, the students were satisfied with the implementation of online exams - Take-Home Exam. The results of this study indicate that UT’s management must make changes and improvements that are oriented towards student satisfaction.